ROLE OF INTERPERSONAL COMMUNICATION IN SANITATION CAMPAIGNS - Varghese, Aswathi Mary; Sharma, Anuradha (International Journal of Psychosocial Rehabilitation, 2020)
India’s vast and diverse socio-cultural and economic composition ensures a heterogeneous populous living in both rural and urban settings. Considering the varied living conditions of people and their different realities, it makes it important to conceive this populous as a group with complex needs that can be met by one homogenous communication strategy or message. Mass media communication channels are typically used in campaigns geared for wide and public audiences, but often campaigns directed to local communities with specifically identified audiences are the most effective in involving citizens in problem-solving and planning decisions that affect their everyday lives clearly outlining the importance Interpersonal Communication (IPC) activities. This study is an attempt to understand the role and functions of Interpersonal Communication approaches adopted during the Awareness Building Phase in ‘Swachh Bharat/Clean India’ Campaign and thereby identify related prospects and problems. To do so, the first section focuses on the theoretical prospective understanding the importance of Interpersonal Communication and strong components of community outreach activities and ground level connect. Further it studies the use of IPC activities based on triggering of community action for provision of sanitation, safe water and hygiene access as part of the above mentioned campaign in two rural villages of India.